Laporan cadangan rekabentuk dalaman bagi “Penang Chinese Restaurant” di Lot 725, Sek 4, Daerah Timur Laut, Georgetown, Pulau Pinang / Natasya Suaid - Suaid, Natasya (Faculty of Architecture, Planning and Surveying, 2004)
This final project is about proposed an interior design scheme a Chinese restaurant at Lot 725, Sek 4, Daerah Timur Laut, Georgetown, Pulau Pinang for the Ministry of Culture, Arts and Tourism Malaysia. This proposal for Penang Chinese Restaurant deals with the initial brief of Penang tourist development for the purpose of enhancing the tourist attraction of the historic and mufti-religious dty. The restaurant proposal is designed to create an environment where people interact through Chinese food and lifestyles. It also can show the truly identity of Penang which is largest ethnic group in this state. Restaurant based on a cultural identity has always been an interesting subject for a design project. This is because it has an element of history, custom, beliefs and unique symbolic representation of the particular race and origin besides other important commercial factors.